Equipment acquisition for Poland - Caban, Dariusz (Zielona Góra: Uniwersytet Zielonogórski)
The TEMPUS projects in general, along with lEP 0449, aim at upgrading the teaching facilities in the Central and East European educational institutions. The actions undertaken to acquire the necessary equipment are presented in this paper. It includes an overview of the developed facilities and the equipment used. Experiences in equipment acquisition and pitfalls are expounded.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka